Hypokalemia induced rhabdomyolysis: a case series from a tertiary health care centre of Bangladesh - Ahmed, Syed Mohaimeen; Azad, Md Rihan; Haque, Md Rezwanul; Khan, Mohammad Sakhawat Hossen; Islam, Md Rashedul (BIRDEM Medical Journal, 2023)
Severe hypokalemia can cause many complications ranging from simple muscle weakness and paralysis with or without respiratory muscle weakness to life threatening cardiac arrhythmia. Rarely, hypokalemia can cause rhabdomyolysis. Acute kidney injury is a potential complication of severe rhabdomyolysis and carries a poor prognosis. Here, we present reports of 3 cases who presented with hypokalemia and developed rhabdomyolysis as a complication. BIRDEM Med J 2023; 13(3): 149-151